Understanding multinational companies in public health systems, using a competitive advantage framework - Lethbridge Jane (BMC, 2011)
Abstract Background This paper discusses the findings of a study which developed five case studies of five multinational health care companies involved in public health care systems. Strategies were analysed in terms of attitude to marketing, pricing and regulation. The company strategies have been subjected to an analysis using Porter's Five Forces, a business strategy framework, which is unusual in health policy studies. Methods This paper shows how analysing company strategy using a business tool can contribute to understanding the strategies of global capital in national health systems. It shows how social science methodologies can draw from business methods to explain company strategies. Results The five companies considered in this paper demonstrate that their strategies have many dimensions, which fit into Porter's Five Forces of comparative advantage. More importantly the Five Forces can be used to identify factors that influence company entry into public health care systems. Conclusions The process of examining the strategic objectives of five health care companies shows that a business tool can help to explain the actions and motives of health care companies towards public health care systems, and so contribute to a better understanding of the strategies of global capital in national health systems. Health service commissioners need to understand this dynamic process, which will evolve as the nature of public health care systems change.